2013
DOI: 10.1149/05804.0033ecst
|View full text |Cite
|
Sign up to set email alerts
|

Packaging Techniques for Compact SiC Power Modules Operable in an Extended Tj Range

Abstract: Packaging technology applicable to SiC power devices operated in an extended junction temperature range (Tjmax > 200°C) must be developed in order to create much more compact and cost-effective SiC power modules. This paper describes some of the technical challenges involved in improving the reliability of the critical package components—die attachment system, Al wire bonds and encapsulation—in direct contact with SiC devices inside the power module. Two numerical targets, (I) 3000 hours for a storage test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The wire bond life determined the power cycle lifetime of the test samples (approximately 35 000 cycles). The PCT results revealed that, within acceptable experimental error, there was little decline in die shear strength until the test ended at 37 421 cycles [38]. A X-SEM of a Au-Ge die attachment after 37 421 PCT cycles showed that there were no signs of thermomechanical fatigue, such as microcracks and folding, in the solder layers.…”
Section: A Die Attachmentmentioning
confidence: 77%
See 4 more Smart Citations
“…The wire bond life determined the power cycle lifetime of the test samples (approximately 35 000 cycles). The PCT results revealed that, within acceptable experimental error, there was little decline in die shear strength until the test ended at 37 421 cycles [38]. A X-SEM of a Au-Ge die attachment after 37 421 PCT cycles showed that there were no signs of thermomechanical fatigue, such as microcracks and folding, in the solder layers.…”
Section: A Die Attachmentmentioning
confidence: 77%
“…5, bond pull strength declined with increasing thermal cycles, albeit the rate of decrease lessened. However, after 3000 cycles, it was at a level of 127 gf, still satisfying the IEC criterion [37] by a sufficient margin [38]. The breakage mode of the wire bond samples subjected to the bond pull test was either beam breakage or heel breakage.…”
Section: B Wire Bondsmentioning
confidence: 97%
See 3 more Smart Citations